Proximal composition and functional properties of lyophilizated surimi of Dosidicus gigas “jumbo squid” - Solari-Godiño, Armando (2017)
The purpose of the research was to determinate proximal composition and functional properties of the giant squid freeze-dried surimi (Dosidicus gigas). Surimi elaborated from giant squid and it lyophilized until obtaining surimi powder to evaluate its characteristics and functional properties. The protein content was 58.7% and carbohydrate 30.5%. Protein solubility in water and salt (3%) were 21.1% and 40.6% respectively, these values being higher than surimi powder of commercial species. The gelling capacity was 2.4% and the emulsifying capacity was 79.9% at a concentration of 1.0%. The color on the Hunter scale was L*: 91.5; a*: 0.5; b*: 7.0. Giant squid powder surimi considered as a functional protein powder due to its percentage protein content, and had good technological characteristics and great potential in the food industry.